Prospective cohort study of neoadjuvant therapy toxicity in the treatment of oesophageal adenocarcinoma. (April 2018) - Bunting, David; Berrisford, Richard; Wheatley, Tim; Humphreys, Lee; Ariyarathenam, Arun; Sanders, Grant
Abstract: Background: Early studies investigating the benefits of neoadjuvant therapy in oesophageal cancer showed conflicting results, taking many years before a survival advantage was demonstrated in randomised trials. Gains are modest, limited by progressive disease and toxicity. This study aimed to investigate the relationship between neoadjuvant therapy-associated toxicity and clinical outcomes including survival in patients with potentially curable oesophageal adenocarcinoma. Materials and methods: A cohort of 286 patients undergoing neoadjuvant therapy followed by surgical resection at a single institution was identified from a prospective database. Adverse events from neoadjuvant therapy were recorded and graded. Patients were divided into two groups according to whether they suffered toxicity or not. Clinical outcomes including whether patients completed the neoadjuvant course, whether they proceeded to resection and overall survival, were compared between the groups. Results: Neoadjuvant therapy-related toxicity was identified in 67/286 patients. 46 patients suffered severe, life-threatening or fatal adverse events. In patients with toxicity, 47% did not complete the chemotherapy course compared to 17% without toxicity, RR 2.7 (95%CI 1.7–4.4), (P < 0.001). In patients suffering toxicity, 17.9% failed to proceed to resection compared with 7.8% in those without toxicity, RR 2.3 (95%CI 1.2–4.6) P = 0.02. Median overall survival was shorter in patients suffering toxicity (20.7 months) compared to those without toxicity (37.8 months), P = 0.008. When patients failing to proceed to resection were excluded, median overall survival was shorter in patients suffering toxicity (26.2 months) compared with those without toxicity (47.8), P = 0.039. Conclusion: Neoadjuvant therapy-related toxicity is common and can have serious consequences including failure to complete chemotherapy cycles, a higher risk of not proceeding to surgical resection and poorer overall survival. Efforts should be made to reduce toxicity and research should aim to identify responders and factors predictive of toxicity. Highlights: Neoadjuvant therapy-related toxicity in oesophageal adenocarcinoma is common. Toxicity is associated with failure to complete chemotherapy courses. Toxicity is associated with a higher risk of not proceeding to surgical resection. Toxicity is associated with poorer overall survival. Factors predictive of toxicity and response to therapy should be identified.